Motivations for personal financial management: A Self-Determination Theory perspective - Di Domenico, Stefano I.; Ryan, Richard M.; Bradshaw, Emma L.; Duineveld, Jasper J. (Frontiers in Psychology, 2022)
Financial knowledge and sound financial decision making are now broadly recognized to be important determinants of both personal and societal prosperity, but research has yet to examine how distinct qualities of motivation may be associated with the way people manage their money. In two studies we applied the framework of Self-Determination Theory (SDT) to examine people’s autonomous (volitional) and controlled (pressured) motivation for understanding and managing their finances, as well as their amotivation (lack of motivation) for doing so, and the differential associations these motives have with financial knowledge and financial well-being. Two online samples of Americans (Study 1, N = 516; Study 2, N = 534) completed a detailed demographic survey and questionnaires assessing the financial variables of interest. As hypothesized, SDT’s motivational constructs were associated with financial outcomes over and above participants’ age, gender, income, household wealth, and educational attainment. Specifically, autonomous motivation was positively associated with a host of positive financial indicators (e.g., saving/investing and financial self-efficacy, well-being, and self-awareness); controlled motivation was negatively associated with financial well-being; and amotivation was positively associated with overspending and negatively with financial self-efficacy and well-being. These findings support the relevance of SDT’s framework in this domain and suggest that interventions aimed at promoting financial knowledge and wellness may benefit by adopting evidence-supported strategies for optimizing more autonomous motivations and addressing amotivations.